Bionanomaterials for environmental and agricultural applications - Singh, Ravindra Pratap Singh; Singh, Kshitij R. B. (IOP (Series). Release 21., 2021)
Providing an extensive review of the latest bionanomaterials research, this book fills a gap for a comprehensive and up-to-date reference text, exploring the prospects and limitations of using bionanomaterials in food processing, water treatment, agricultural yield, food quality, environmental monitoring, pollution and other related areas in environmental and agricultural science. Particular attention is given to sensors, adhesives and fibers, and their use in diverse disciplines such as biomedicine, environmental science and agriculture.